काव्यप्रकाशाचमनम् (प्रथमाचमनम्) - Lalit Patel; Pankaj Rawal (Shree Somnath Sanskrit University Junagadh Gujarat, 2013)
The Kavyaprakashachamanam is based on kavyaprakasha which is a Sanskrit book written by Mammaṭa in the 11th century.
Kavyaprakashachamanam (Prathamachamanam)
Keywords: काव्यप्रकाशाचमनम् (प्रथमाचमनम्); Kavyaprakashachamanam (Prathamachamanam); Literature; Sanskrit